The identification of Diptera of the grave and their succession patterns during winter and summer in central South Africa, with reference to forensic applications - Van der Merwe, Sylvia Shalomé (University of the Free State, 2016)
English: Forensic entomology is a specialist branch of forensic sciences in which information about insects is used to draw certain conclusions when investigating medico-legal cases involving both humans and wildlife. The primary application of insects collected from a crime scene is to determine the Post-Mortem Interval (PMI). One of the principal cornerstones in the effective application of forensic entomology is the correct identification of species found at a crime scene. The estimation of PMI using succession and developmental data is dependent upon the specific species that were present on a cadaver. The aim of this study was to identify the members of the Diptera that are capable of colonising buried carrion within a Free State grassland area, as well as to compare below ground dipteran data with above ground dipteran succession patterns. The field experiments, conducted in order to determine what species of Diptera are capable of reaching buried carrion during winter and summer months, as well as to determine the succession patterns of Diptera on buried remains, were conducted on the west fields of the University of the Free State campus, in central South Africa. The area is characterised by dry mild winters and warmer summers, with occasional rainfall periods. A total of seven pigs (Sus scrofa Linnaeus 1758) were used during each season, which consisted of one above ground control carcass and six separate below ground carcasses buried at 60 cm. Below ground carcasses were left for predetermined periods of time and were excavated on separate occasions over each 120 day trial period to monitor dipteran occurrence, colonisation and dipteran interactions. Members of Diptera were found to colonise carcasses at 60 cm during both winter and summer trials. Higher dipteran species diversity was noted on the buried winter carcasses in comparison to the buried summer carcasses. Four species of Diptera, Megaselia scalaris (Loew 1866) (Phoridae), Conicera tibialis Schmitz 1925 (Phoridae), Muscina stabulans (Fallén 1817) (Muscidae) and Leptocera Olivier 1813 sp. (Sphaeroceridae) were seen to occur on winter carcasses, with first colonisation taking place from day 21 of the winter trial. Three species of the Diptera, M. scalaris, Leptocera sp., and Sarcophaga Meigen 1826, were seen to colonise buried summer carcasses, with first colonisation taking place from day 21 of the summer trial. Dipteran faunal composition on buried carcasses was noted to be different to that of Diptera on above ground carcasses during both the winter and the summer trials. Statistical analysis showed that there was a significant difference between above ground and below ground dipteran faunal similarity. Preservation experiments on immature Diptera of the grave for identification purposes showed that the standard preservation mediums used for insects of forensic importance, such as ethanol solution and formaldehyde solution, are not effective. Preservation of adult samples was successful in 70% ethanol solution. Breeding trials under laboratory conditions proved effective in breeding larval instars found on buried carcasses through to adulthood for identification. Due to the difficulty in preservation of immature individuals of Diptera of the grave, and the ease of breeding larvae of these dipteran species, identifications were done on adult specimens. Adult Diptera were described based on taxonomic criteria, including wing venation, setal hairs and the hypopygium of male phorid specimens, and a simplified identification key was successfully compiled using morphology of the adult Diptera of the grave.

Afrikaans: Forensiese entomologie is ‘n spesialisafdeling van forensiese wetenskap waar inligting aangaande insekte gebruik word om sekere afleidings aangaande medies-regsgeldige sake te maak waar beide mense en diere betrek is. Die primêre aanwending van insekte wat op ‘n misdaadtoneel versamel is, is om die Post-Mortem Interval (PMI) te bepaal. Een van die grondslag beginsels in die doeltreffende aanwending van forensiese entomologie is die noukeurige identifikasie van spesies wat op die misdaadtoneel aangetref word. Die PMIbepaling deur middel van suksessie- en ontwikkelingsdata, is afhanklik daarvan om die spesifieke spesies wat op die kadawer teenwoordig is te gebruik. Die doel van die huidige studie was om verteenwoordigers van die Diptera te identifiseer wat in staat is om aas wat begrawe is te koloniseer binne ‘n Vrystaat-graslandgebied, sowel as om die data van ondergrondse Diptera met die suksessiepatrone van bogrondse Diptera te vergelyk. Die veldeksperimente, uitgevoer om te bepaal watter spesies van Diptera in staat is om aas wat begrawe is tydens winter- en somermaande te bereik, sowel as die bepaling van die suksessiepatrone van Diptera op oorskot wat begrawe is, is uitgevoer op die westelike velde van die Universiteit van die Vrystaat-kampus in sentraal Suid-Afrika. Hierdie gebied word deur droë, gematigde winters en warmer somers, met toevallige reënvalperiodes gekenmerk. ‘n Totaal van sewe varke (Sus scrofa Linnaeus 1758) is tydens elke seisoen gebruik, wat uit een bogrondse kontrole-karkas en ses aparte karkasse begrawe op 60 cm bestaan het. Karkasse wat begrawe is, is vir voorafbepaalde periodes gelaat en dan weer opgegrawe op verskillende tye oor ‘n 120-dae proefperiode ten einde die voorkoms, kolonisering en interaksies van Diptera te monitor. Verteenwoordigers van Diptera is bevind om karkasse op 60 cm tydens beide die winter- en somerproewe te koloniseer. Hoër spesieverskeidenheid van Diptera is op die winterkarkasse wat begrawe is gevind, in vergelyking met die somerkarkasse wat begrawe is. Vier Diptera spesies, Megaselia scalaris (Loew 1866) (Phoridae), Conicera tibialis Schmitz 1925 (Phoridae), Muscina stabulans (Fallén 1817) (Muscidae) en Leptocera Olivier 1813 sp. (Sphaeroceridae) is op die winterkarkasse waargeneem, met eerste kolonisering vanaf dag 21 tydens die winterproef. Drie Diptera spesies, M. scalaris, Leptocera sp., en Sarcophaga Meigen 1826, is op somerkarkasse wat begrawe is waargeneem, met eerste kolonisering wat op dag 21 van die somerproef voorgekom het. Die faunasamestelling van Diptera op karkasse wat begrawe was, is bevind om te verskil van dié van Diptera op bogrondse karkasse tydens beide die winter- en somerproewe. Statistiese analise het getoon dat daar ‘n wesenlike verskil tussen die Diptera-ooreenkoms bogronds en ondergonds was. Preserverings-eksperimente op onvolwasse Diptera-van-die-graf vir identifikasie-doeleindes het getoon dat die standaard preserveringsmediums wat vir insekte van forensiese belang gebruik word, soos etanol- en formaldehiedoplossings, nie effektief was nie. Die preservering van volwasse monsters was wel suksesvol deur van 70% etanol gebruik te maak. Uitbroeiproewe onder laboratoriumtoestande het getoon om effektief te wees in die uitbroei van larwale instars na volwassenes vir identifikasie vanaf karkasse wat begrawe was. As gevolg van die probleme wat ondervind is om onvolwasse individue van Diptera-van-die-graf te preserveer, en die gemak om larwes van hierdie Diptera-spesies uit te broei, is identifikasies uitgevoer deur van volwasse eksemplare gebruik te maak. Volwasse Diptera-eksemplare is beskryf gebaseer op taksonomiese kriteria wat vlerkbearing, seta-hare en die hipopigium van manlike eksemplare van die Phoridae ingesluit het. Verder is ‘n vereenvoudigde identifikasie-sleutel suksesvol opgestel deur van die morfologie van volwasse Diptera-van-die-graf gebruik te maak.
Keywords: Dissertation (M.Sc. (Zoology and Entomology))--University of the Free State, 2016; Diptera; Morphology; Morphological key; Forensic entomology; Phoridae